Competition of irrigated wheat varieties at Sete Lagoas - Coqueiro, Erycson Pires; Silva, Jairo; Andrade, José Maria Vilela de (Pesquisa Agropecuaria Brasileira, 2014)
Twelve varieties of wheat were tested during 1967 to 1969, in Sete Lagoas, Minas Gerais. The varieties were selected by the Subcomissão Norte de Trigo, Departamento Nacional de Pesquisa Agropecuária through experimental results and other information available in 1967. Observed average grain yields show the possibility of production higher than 3.000 ton/ha. IAS 49, Pel A 407-61 and IAS 50 were indicated as best of all varieties through studies in production consistency from years to year, resistance to stem rust and lodging. In addition to grain production, other factors considered and presented are: crop cycle, resistance to stem rust, plant height, lodging, test weight per hectoliter and protein content.